2020
DOI: 10.1002/cjp2.190
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐exome sequencing analysis of juvenile papillomatosis and coexisting breast carcinoma

Abstract: Juvenile papillomatosis (JP) of the breast is a rare benign mass‐forming lesion occurring in young women, which is histologically characterized by a constellation of proliferative changes and large cysts, giving it the gross appearance of Swiss cheese. A subset of patients with JP report a family history of breast carcinoma and/or coexisting or subsequent breast carcinoma. We performed whole‐exome sequencing of the hyperplastic epithelial component of three JPs, including one with coexisting ductal carcinoma i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…RNA sequencing, which can be applied to identify the tumor driver genes, not only brought incredible changes and advantages in the field of tumor [ 17–19 ], but expands understanding and provides potential treatment strategies for some special types of tumors, such as inflammatory breast cancer and juvenile papillomatosis with co-existing breast carcinoma [ 20 , 21 ]. In our study, we found 3764 DE mRNAs, 5416 DE lncRNAs, and 148 DE circRNAs by RNA sequencing in three breast cancer tissues compared with their paired normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…RNA sequencing, which can be applied to identify the tumor driver genes, not only brought incredible changes and advantages in the field of tumor [ 17–19 ], but expands understanding and provides potential treatment strategies for some special types of tumors, such as inflammatory breast cancer and juvenile papillomatosis with co-existing breast carcinoma [ 20 , 21 ]. In our study, we found 3764 DE mRNAs, 5416 DE lncRNAs, and 148 DE circRNAs by RNA sequencing in three breast cancer tissues compared with their paired normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…2 Another recent study identified clonal somatic PIK3CA hotspot mutations in 2 of 3 cases of juvenile papillomatosis, including 1 with an associated ductal carcinoma in situ and invasive ductal carcinoma. 3 Interestingly, the in situ and invasive carcinomas and the juvenile papillomatosis had a somatic clonal PIK3CA E542K hotspot mutation. 3…”
mentioning
confidence: 99%
“…3 Interestingly, the in situ and invasive carcinomas and the juvenile papillomatosis had a somatic clonal PIK3CA E542K hotspot mutation. 3…”
mentioning
confidence: 99%